2020
DOI: 10.1021/acs.langmuir.0c02894
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Nucleoside-Derived Low-Molecular-Weight Gelators: A Thermodynamics and Kinetics Study on Different Length Scales

Abstract: Biocompatible materials are of paramount importance in numerous fields. Unlike chemically-bridge polymer-based hydrogels, low molecular weight gelators can form a reversible hydrogel as their structure rely on non-covalent interaction. Although many applications with this type of hydrogels can be envisioned, we still lack their understanding due to the complexity of their self-assembly process and the difficulty predicting their behaviors (transition temperature, gelation kinetic, impact of solvent…). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…These results show that their kinetics give enough time for the gels to slightly cool down and for the experimenter to stir together the LMWG solution with the cells before the gelation occurs. It is noteworthy that the induction time for BU and BA corresponds to the supercooling time as it was shown that these hydrogels undergo non-isothermal gelation during cooling …”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results show that their kinetics give enough time for the gels to slightly cool down and for the experimenter to stir together the LMWG solution with the cells before the gelation occurs. It is noteworthy that the induction time for BU and BA corresponds to the supercooling time as it was shown that these hydrogels undergo non-isothermal gelation during cooling …”
Section: Results and Discussionmentioning
confidence: 99%
“…It is noteworthy that the induction time for BU and BA corresponds to the supercooling time as it was shown that these hydrogels undergo non-isothermal gelation during cooling. 42 Porosity and Molecular Diffusion Timescales. To host cells for culture, the matrix must permit molecular mobility through it, small molecules to biomolecules.…”
Section: Right)mentioning
confidence: 99%
See 3 more Smart Citations